2022
DOI: 10.1371/journal.pone.0269249
|View full text |Cite
|
Sign up to set email alerts
|

Target and drug predictions for SARS-CoV-2 infection in hepatocellular carcinoma patients

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the coronavirus disease (COVID-19), which poses a major threat to humans worldwide. With the continuous progress of the pandemic, a growing number of people are infected with SARS-CoV-2, including hepatocellular carcinoma (HCC) patients. However, the relationship between COVID-19 and HCC has not been fully elucidated. In order to provide better treatment for HCC patients infected with SARS-CoV-2, it’s urgently needed to identify commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Although COVID-19 primarily affects the respiratory system, liver dysfunction is also common in COVID-19 patients, such as elevated liver transaminases and elevations of cholestatic liver enzymes(30). The association between the most common liver cancer, HCC, and COVID-19 has been reported in a previous article (9). ICC, which is the second most common liver cancer and has many similarities with HCC, may also be linked to COVID-19.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although COVID-19 primarily affects the respiratory system, liver dysfunction is also common in COVID-19 patients, such as elevated liver transaminases and elevations of cholestatic liver enzymes(30). The association between the most common liver cancer, HCC, and COVID-19 has been reported in a previous article (9). ICC, which is the second most common liver cancer and has many similarities with HCC, may also be linked to COVID-19.…”
Section: Discussionmentioning
confidence: 58%
“…Liver cancer is the sixth most common and the third deadliest malignancy in the world (8). The relationship between COVID-19 and hepatocellular carcinoma (HCC), the most common form of liver cancer, has been reported recently (9). As the second most common liver cancer, ICC is highly similar with HCC, which are both associated with cirrhosis, infection of Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV), and metabolic syndrome (10).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the Introduction, we carefully selected 11 projects [13][14][15][16][17][18][19][20][21][22][23] out of the 18 projects identified in the scientific literature between 2021 and 2023. These papers deal with the characterization of hepatic metabolic processes that are viral targets in patients affected by COVID-19.…”
Section: Hub Data Of Human Liver During Covid-19mentioning
confidence: 99%
“…Some of our searches on PubMed performed using terms such as "COVID-19 AND liver hub genes" or similar terms, extracted eighteen studies, of which we selected eleven (2021-2023) [13][14][15][16][17][18][19][20][21][22][23] because they reported hub genes linked to COVID-19 (see also in the Results). These studies aim to determine regulatory processes from datasets based on microarray or transcriptome sequencing technology.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on PubMed [11,[13][14][15][16][17][18][19][20][21][22] from 2021 to 2023 reported hub genes linked to COVID-19. They aim to determine regulatory processes from datasets based on microarray or transcriptome sequencing technology.…”
Section: Introductionmentioning
confidence: 99%